'Pink rot': infection of Castanea sativa fruits by Colletotrichum acutatum. Issue 2 (24th September 2016) - Gaffuri, F.; Longa, C.M.O.; Turchetti, T.; Danti, R.; Maresi, G.
Summary: Pink‐coloured tissues were observed in rotting chestnut nuts collected from soil in different orchards in Italy (Emilia Romagna, Tuscany and Trentino). Morphological and molecular analysis confirmed the presence of Colletotrichum acutatum (J.H. Simmons) in affected fruits, and inoculation tests corroborated the ability of the pathogen to colonize nuts.